Critical analysis of phase II and III randomised control trials (RCTs) evaluating efficacy and tolerability of a β3‐adrenoceptor agonist (Mirabegron) for overactive bladder (OAB). (27th July 2014) - Rossanese, Marta; Novara, Giacomo; Challacombe, Ben; Iannetti, Alessandro; Dasgupta, Prokar; Ficarra, Vincenzo
<x xml:space="preserve">Abstract</x> To critically analyse available phase II and III randomised control trials (RCTs) reporting clinical data about the efficacy and tolerability of Mirabegron (a β3‐adrenoceptor agonist) in the treatment of overactive bladder (OAB) syndrome. A review of the literature was performed in September 2013 using the MEDLINE database. A 'free text' protocol was used for the search strategy using 'overactive bladder' and 'Mirabegron' as keywords. Subsequently, the searches were pooled and limited to phase II and III RCTs. Two phase II and five phase III RCTs were selected and analysed. The available phase II studies showed the efficacy and tolerability of different doses of Mirabegron compared with placebo. Moreover, a dose‐ranging study showed that 50 mg once daily should be considered the most promising dose for clinical use. The 12‐week phase III studies confirmed the effectiveness of Mirabegron to significantly reduce the mean number of incontinence episodes/24 h and the mean number of micturitions/24 h compared with placebo. A post hoc analysis confirmed that favourable results with Mirabegron were reported both in patients with OAB who were antimuscarinic naïve and in those who had discontinued prior antimuscarinic therapy. Moreover, a phase III trial showed the safety and tolerability of 12‐month treatment of Mirabegron. Discontinuation due to adverse events was low both using the 50 and 100 mg dose of Mirabegron. Mirabegron is the first of a new class of drugs for the treatment of OAB able to influence non‐voiding activity and produce an increased storage capacity and inter‐void interval. Recently published phase II and III RCTs have shown that the β3‐adrenoceptor‐selective agonist, Mirabegron, is an effective and safe drug for the symptomatic treatment of OAB syndrome. Mirabegron represents a valid medical option both for patients with OAB who are antimuscarinic naïve, as well as in those where antimuscarinics are ineffective or not tolerated.